The Use of News Reports to Predict the Values of Macroeconomic Indicators and Indices Represented by Time Series - Artur Mikhailov; Natalia Gergel (Proceedings of the International Conference on Applied Innovations in IT, 2018)
The use of forecasts and predictive models highly affects the process of making decisions. The use of given forecasts allows to increase economic effectiveness of individual entities as well as the corporations. The aim of the article is the investigation of the influence of the weakly formalized factors on the forecasts' accuracy. The study is based on the problem of classification for determining the trends of changing the indicators and the levels of external factors’ influences on a change of the referencing parameter. The dataset which contains 25 daily news headings gathered during 8 years was used to make the calculations. The chosen news headlines are related to the stock market and were published by the most authoritative sources such as: Russia Today, Reuters, Scientific American, The Guardian. It was demonstrated that the record of the influence of the information in the news reports on the change of the referencing parameter (using the example of the NASDAQ index) allows clarifying the forecasts taken with the use of functional methods. Therefore, it leads to minimizing mistakes and maximizing the forecasts’ reliability.